MODEL KOMUNIKASI DIALEKTIKA: KONVERSI BANK NAGARI KONVENSIONAL MENJADI BANK NAGARI SYARIAH DI SUMATERA BARAT - Rahmat Saleh; Aidinil Zetra; Roni Ekha Putera (Jurusan Ilmu Komunikasi Universitas Andalas, 2023)
This article discusses the dialectical communication model between structure and agency in realizing the conversion of Bank Nagari from Conventional Bank to Bank Nagari Syariah. It employs a qualitative research method through interviews and informant triangulation. Communication plays a crucial role in achieving the conversion of Bank Nagari from a conventional model to a Sharia model. The Governor has the opportunity to communicate explicitly and implicitly with regional heads in implementing the conversion process. The dynamics of the relationship between structure and agency also influence different communication patterns depending on specific situations and conditions. The lack of understanding regarding the significance of converting Bank Nagari into a Sharia bank is related to cultural elements, values, beliefs, and individual interests, leading to diverse perspectives. Marsh and Smith's theory emphasizes that the interaction between structure and agency should be seen as entities with variations in terms of culture, values, beliefs, attitudes, behaviours, and interests. The conclusion of this article is the presence of implicit and explicit communication in the conversion of Bank Nagari, the role of Datuk as an opinion leader, and OJK communication with the Governor.